Tinjauan Pustaka Senyawa Metabolit Bioaktif Daun Sambiloto (Andrographis paniculata) sebagai Agen Terapi - Mirna Saputri Pratama; Ardi Mustakim (CV. Muara Edukasi, 2026)
Sambiloto (Andrographis paniculata) leaves are widely recognized as medicinal plants used in traditional therapy due to their rich content of bioactive secondary metabolites. Several bioactive compounds found in sambiloto leaves include andrographolide, flavonoids, phenolics, tannins, and alkaloids, which play important roles in therapeutic activities. One of the main issues is the lack of integrated reviews linking these bioactive metabolites with their potential use as therapeutic agents. This study aims to review the bioactive metabolite compounds of A. paniculata leaves and their roles in therapeutic applications. The method used was a literature review by analyzing various national and international scientific articles related to metabolite content and pharmacological activities of sambiloto leaves. The results indicate that phenolic compounds, flavonoids, and tannins contribute to antioxidant and anti-inflammatory activities, while andrographolide and alkaloids are associated with antimicrobial, antidiabetic, and immunomodulatory effects. In conclusion, sambiloto leaves have strong potential to be developed as natural therapeutic agents based on their bioactive secondary metabolites